2015
DOI: 10.1017/s1368980015002529
|View full text |Cite
|
Sign up to set email alerts
|

Formulating policy activities to promote healthy and sustainable diets

Abstract: Objective: To develop a policy formulation tool for strategically informing food and nutrition policy activities to promote healthy and sustainable diets (HSD). Design: A policy formulation tool consisting of two complementary components was developed. First, a conceptual framework of the environment-public health nutrition relationship was constructed to characterise and conceptualise the food system problem. Second, an 'Orders of Food Systems Change' schema drawing on systems dynamics thinking was developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 52 publications
1
59
0
2
Order By: Relevance
“…Our scenario modelling results suggest that agriculture will continue to be a substantial contributor to increased GHG emissions and environmental resource use. Results also suggest that Australia may become increasingly reliant on imported fruit, nuts, fish and dairy, which in the event of global food system 'shocks' has the potential to undermine future food security and nutrition (Ericksen, 2008;Lawrence et al, 2015). These results support criticisms that Australia's national food and agricultural policies have focused on the economic value of food production and trade at the expense of public health and environmental sustainably Lawrence et al, 2012;Ridgway et al, 2015).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 53%
“…Our scenario modelling results suggest that agriculture will continue to be a substantial contributor to increased GHG emissions and environmental resource use. Results also suggest that Australia may become increasingly reliant on imported fruit, nuts, fish and dairy, which in the event of global food system 'shocks' has the potential to undermine future food security and nutrition (Ericksen, 2008;Lawrence et al, 2015). These results support criticisms that Australia's national food and agricultural policies have focused on the economic value of food production and trade at the expense of public health and environmental sustainably Lawrence et al, 2012;Ridgway et al, 2015).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 53%
“…Sustainable eating is therefore essential not only in terms of food and nutrient safety [20,21], but also on the social level [22,23]. That is why numerous recommendations and studies advise to policy makers in food security and sustainability regulation to integrate direct, indirect or voluntary tools into the social framework for sustainable food consumption [20,[24][25][26][27][28][29][30].…”
Section: A Few Aspects Of the Sustainability Dimensionmentioning
confidence: 99%
“…Lawrence et al . () showed how important food and nutrition policy activities are to the redesign of the food system needed to promote healthy and sustainable diets. Food policies need to account for how people – citizens, communities – are affected by the food system problems we are seeking to address (Hawkes ).…”
Section: Policy and Sustainabilitymentioning
confidence: 99%
“…Advice from dietitians and nutritionists should be based on government policies in the area, and also the policies of the communities they are working with (BDA 2013(BDA , 2017AfN 2018a,b). Lawrence et al (2015) showed how important food and nutrition policy activities are to the redesign of the food system needed to promote healthy and sustainable diets. Food policies need to account for how peoplecitizens, communitiesare affected by the food system problems we are seeking to address (Hawkes 2018).…”
Section: Policy and Sustainabilitymentioning
confidence: 99%